Impact of dried apple pomace on the quality of gluten-free bread - Hryshchenko, Anna; Levtseniuk, Leonid; Hanzyna, Bohdan; Banakh, Yevhen (My University, 2022)
З метою підвищення вмісту харчових волокон в безглютеновому хлібі досліджено вплив сушених яблучних вичавок різних виробників та різної дисперсності на показники його якості. Встановлено, що у разі дозування 2-8% вичавків призводить до зменшення питомого об’єму виробів, затемнення скоринки та м’якушки хліба та погіршення пористості в різній степені.

To increase the dietary fiber content in gluten-free bread, the effect of dried apple pomace from different producers and different dispersions on its quality indicators was investigated. It was found that in the case of a dosage of 2-8% of the pomace, it leads to a decrease in the specific volume of the products, darkening of the crust and crumb of the bread, and deterioration of the porosity to varying degrees.
Keywords: ксантанова камедь; безглютеновий хліб; сушені яблучні вичавки; рисове борошно; xanthan gum; gluten-free bread; dried apple pomace; rice flour; starch; кафедра технології хлібопекарських і кондитерських виробів